Studies on Accurate Differentiation of Dyssynergic Defecation Patients from Normal Subjects Based on Abnormal Anorectal Angle in MR Defecography - Afsaneh Nikjooy; Nader Maroufi; Esmaeil Ebrahimi; Homayoun Hadizadeh Kharazi; Bahar Mahjoubi; Hamidreza Saligheh Rad (Challenges in Disease and Health Research Vol. 7, 2021)
Objective: We aimed to study the kinematic indices of the pelvic floor, anorectal angle and the descent of perinea, and the differing movement, in dyssynergic defecation patients in comparison with healthy controls, based on MR defecography. Methods: Twenty-two individuals involved with dyssynergic defecation constipation and fourteen healthy asymptomatic subjects fell into this study. In four dynamic pelvic floor MRI indices, namely paradox (unusual change of anorectal angle), perineal descent during straining, perineal ascent, and narrowing of anorectal angle at squeeze, were measured in patients and healthy subjects. Results: Paradox Index had the highest sensitivity (95.45%) and specificity (92.86%) for detection of dyssynergic defecation, with an R2 value of near 1 (0.902). The sensitivity and specificity of other indices were not high; therefore, no significant improvement could be achieved using other indices along with Paradox Index. Negative Predictive Value (92.85%) and Positive Predictive Value (95.45%) were only high in Paradox Index. Conclusion: Paradox Index was indicated to be the best finding of MR defecography for identifying dyssynergic defecation patients from healthy controls. Hence, MR defecography could be exploited as an authentic tool to manifest the patients the paradoxical function and the relevant muscles of pelvic floor, which could enhance their imagination of the correct defecation pattern during their treatment.